2022
DOI: 10.3390/nu14224764
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices of Digestive Surgeons concerning Specialized Nutritional Support in Cancer Patients: A Survey Study

Abstract: A survey study based on a 21-item questionnaire was conducted to assess knowledge and practices of digestive surgeons focused on nutritional support in gastrointestinal cancer patients. At least 5 staff digestive surgeons from 25 tertiary care hospitals throughout Spain were invited to participate and 116 accepted. Malnutrition was correctly defined by 81.9% of participants. In patients undergoing major abdominal surgery, 55.2% considered that preoperative nutritional support is indicated in all patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…A national, representative, cross-sectional survey from China (1732 participants from 51 clinics/hospitals) identified the lack of education and training of healthcare staff in the use of clinical guidelines as a key barrier to guideline implementation, while experience with evidence-based medicine in education and practice was significantly associated with self-reported guideline adherence [ 34 ]. Durán-Poveda et al also confirmed in their survey that there is little knowledge among medical staff about nutritional guidelines and that, therefore, evidence-based nutrition therapy can be offered to cancer patients far too seldom [ 35 ]. Better education and further training of healthcare staff might, therefore, be an important target point to optimize guideline implementation in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A national, representative, cross-sectional survey from China (1732 participants from 51 clinics/hospitals) identified the lack of education and training of healthcare staff in the use of clinical guidelines as a key barrier to guideline implementation, while experience with evidence-based medicine in education and practice was significantly associated with self-reported guideline adherence [ 34 ]. Durán-Poveda et al also confirmed in their survey that there is little knowledge among medical staff about nutritional guidelines and that, therefore, evidence-based nutrition therapy can be offered to cancer patients far too seldom [ 35 ]. Better education and further training of healthcare staff might, therefore, be an important target point to optimize guideline implementation in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the answers to the survey highlighted that nutritional support is not yet fully managed consistently with the available guidelines. Finally, a survey based on a 21-item questionnaire highlighted that digestive surgeons have a limited knowledge of basic aspects of clinical nutrition in gastrointestinal cancer patients, even if with some variability regarding the clinical practice in individual cases [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is a common problem in patients with cancer and is associated with increased risk of complications and reduced tolerance of anti-cancer treatment. [ 26 , 27 ] Previous studies have also shown that comfort nursing can significantly reduce the incidence of postoperative complications, improve the safety of surgical treatment, and reduce anxiety and depression in patients. [ 12 , 13 ] These results consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%